(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In the present work synthesize of LaCoO3 nanomaterial via solgel self ignition mehod with various water flow rates of 0.050; 0.10; and 0.20 kg/min. Nanomaterial blended with black paint coated int the basin area of the the proposed double slope system The morphological and structural properties is examined by the XRD & SEM. Prepared material having structure of porous and crystalline with 86%. Those material enhanced the heat transfer distiller achieved the productivity of 5.40 and 3.85 kg/ m2 . day with and without coating respectively. They used Dunkle correlation to analyze theoretically. Porous wick materials helps to separate the water droplet.